Serum calcium and phosphorous balance in diabetic nephropathy and its correlation with glycated hemoglobin - Kavuparambil, Liji; P., Ashok Kumar; K., Jithesh T.; Kollathodi, Shifa (International Journal of Advances in Medicine, 2021)
Background: Timely control of hemoglobin A1c (HbA1c) level is very important in patients with diabetic kidney disease. Diabetic nephropathy brings changes in mineral metabolism. The changes in calcium and phosphorous level is a reason for increased morbidity or decreased quality of life in these patients. Conflicting reports are available on serum calcium level and decline in kidney function. This study is to analyse the changes in calcium and phosphorous level in different stages of diabetic nephropathy and its correlation with glycated haemoglobin. Methods: A cross sectional study with 60 diabetic nephropathy patients admitted in MES Medical College for a period of 1.5 years. Patients with cardiac, liver, thyroid dysfunction, under dialysis were excluded from the study. Fasting blood sugar, HbA1c, calcium, phosphorous, creatinine were assessed by VITROS 5600 integrated system. The study population is divided into groups by two different means, according to HbA1c and estimated glomerular filtration rate (eGFR) value. Statistical analysis was performed by statistical package for the social sciences (SPSS) software. Level of significance calculated at 95%. Results: eGFR value showed a highly significant correlation with age (p=0.016), creatinine (p≤0.00001), calcium (p≤0.00001), phosphorous (p≤0.00001) and HbA1c (p=0.00001). There was no significant difference in creatinine and eGFR between male and female subjects. Only eGFR (p=0.0396) showed a significant difference between poor and good glycaemic control groups. Conclusions: This study shows highly significant correlation between the decreased eGFR hypocalcaemia, hyperphosphatemia, increased serum creatinine level and HbA1c. Strict glycemic control is crucial in maintenance of mineral homeostasis and prevention of blood calcium, phosphorous abnormalities.